The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ijcp.14123
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusion as an indicator for the poor prognosis of COVID‐19 patients

Abstract: Background Coronavirus Disease 19 (COVID‐19) is a global health concern that has become a pandemic over the past few months. This study aims at understanding the clinical manifestations of COVID‐19 patients with pleural effusion. Methods COVID‐19 patients were retrospectively enrolled from the Union Hospital, Tongji Medical College, Huazhong University of Science and Technology. Pharyngeal swabs from patients were tested using real‐time polymerase chain reaction. Patients with COVID‐19 were divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
(27 reference statements)
1
22
1
1
Order By: Relevance
“…We present a case of pleural effusion in a COVID-19 female patient, in whom pleural effusion developed at a later stage of the progression of disease (Figure 2), which coincides with what Salehi et al reported in their study [6], while Zhang et al reported on a case of COVID-19 with pleural effusion as an initial symptom [12]. Song et al found that pleural effusion resolved after two days [10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We present a case of pleural effusion in a COVID-19 female patient, in whom pleural effusion developed at a later stage of the progression of disease (Figure 2), which coincides with what Salehi et al reported in their study [6], while Zhang et al reported on a case of COVID-19 with pleural effusion as an initial symptom [12]. Song et al found that pleural effusion resolved after two days [10].…”
Section: Discussionsupporting
confidence: 88%
“…Prikazujemo slučaj pleuralnog izliva kod bolesnice obolele od KOVID-19 oboljenja kod koje se pleuralni izliv javio kasnije u toku progresije bolesti (Slika 2), što je u skladu sa izveštajem Salehija i saradnika [6], dok su Žang i saradnici prikazali slučaj KOVID-19 oboljenja sa pleuralnim izlivom kao inicijalnim simptomom [12]. Song i saradnici izveštavaju da se pleuralni izliv apsorbuje već nakon dva dana [10].…”
Section: Diskusijaunclassified
“…Furthermore, although beyond the scope of this study, we need to recode the role that LUS has outside the diagnosis or monitoring of COVID-19 patients. LUS is also useful as a guiding tool during invasive procedures: LUS is a particularly suitable tool for bedside procedures, such as the drainage of pleural effusions that complicate the course of COVID-19 patients in a not-so-small percentage [ 2 , 22 ]. This result is particularly relevant if we consider the logistical difficulties of moving a highly infectious patient to the Radiology Department [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The typical pattern at the chest CT is represented by bilateral interstitial involvement sometimes with consolidative abnormalities. Additional features found in some patients are septal thickening superposes on the ground glass opacification (crazy pattern), bronchiectasis, pleural effusion, 19 pericardial effusion and lymphadenopathy. The lung involvement is almost always bilateral, with the prevalence of peripheral distribution and focused at the lower lobes of the lungs, at least in the less severe conditions.…”
Section: Introductionmentioning
confidence: 99%